EVALUATING THE ASSOCIATION BETWEEN EARLY CHILDHOOD SCREEN EXPOSURE AND AUTISM SPECTRUM DISORDER (ASD): DISENTANGLING CORRELATION AND CAUSATION (Journal of Medical & Health Sciences Review, 2025)
There has been an upsurge in Autism Spectrum Disorder (ASD) and the proportional rise in early exposure to screens has resulted in developmental concerns. The research question of the present study is whether there is a relationship between the early screen exposure and ASD characteristics, which would help in separating correlation and causation. Being a new mom who knows little about the dangers of exposure to different screens at such an early stage of their development, the reasons behind the choice of research are a necessity to understand how the exposure to screens influences the neurodevelopment of young children. Data were gathered with 160 parents of children between 2 and 6 years of age through the use of a quantitative and cross-sectional design using a stratified sampling question. Findings indicated that there was a strong positive relationship between increased screen exposure and high ASD-like behavior; causation, however, is not conclusively possible. It seeks to educate the parents and caregivers on the consequences of limiting exposure to screen time at early stages of their life thus reducing the development risk of the brain.